Analisis Disonansi Kognitif Perokok terhadap Produktivitas di Usia Produktif - Gusti Aulia Ryansyah; Gina Aulia Qotrunnada; Dini Safitri; Triworo Ardhaniswari (Communications, 2024)
Smoking, including cigarettes and other types of tobacco, is harmful to health. Secondhand smoke from cigarettes can be harmful to both active smokers (those who smoke) and non-smokers (those who inhale second-hand smoke). Cognitive dissonance is a feeling of irrationality in which a person finds himself doing something inconsistent with his knowledge or acting contrary to what he believes. In this study, methods were used to define the qualitative method. This research focused on determining smoking behavior and production during the productive years. Surveys were used to collect data. The interview method of data collection is done by asking a series of questions related to the research. “Differential Effects of Tobacco Exposure During Manufacturing on Productivity'' shows the relationship between smoking and productivity during manufacturing. According to the results of studies included in this study, it was revealed that smokers experience cognitive dissonance. to. The gap between knowledge about the negative effects of smoking and current smoking behavior may hinder their performance.